2021
DOI: 10.3390/ma14185414
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Biochar-Modified Cementitious Composites Exposed to High Temperatures

Abstract: In this study, the effect of biochar on the high temperature resistance of cementitious paste was investigated using multiple experimental methods. The weight loss, cracks, residual compressive strength, and ultrasonic pulse velocity (UPV) of biochar cementitious paste with 2% and 5% biochar exposed to 300, 550 and 900 °C were measured. The products and microstructures of biochar cementitious paste exposed to high temperatures were analyzed by X-ray diffraction, Fourier transform infrared spectroscopy, thermog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Figure 3c shows the FTIR spectra of SDBC, RSBC and CSBC. The broadband at 3430 cm −1 indicates phenolic hydroxyl groups or carboxylic acids in biochar (Liu, Ye, et al, 2022), and the absorption peak near 3640 cm −1 is the stretching vibration of ‐OH in CH (Yang et al, 2021). The prominent peak at 1050–1100 cm −1 corresponds to the ‐OH vibration of cellulose, with higher absorption observed in RSBC and CSBC (Liu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3c shows the FTIR spectra of SDBC, RSBC and CSBC. The broadband at 3430 cm −1 indicates phenolic hydroxyl groups or carboxylic acids in biochar (Liu, Ye, et al, 2022), and the absorption peak near 3640 cm −1 is the stretching vibration of ‐OH in CH (Yang et al, 2021). The prominent peak at 1050–1100 cm −1 corresponds to the ‐OH vibration of cellulose, with higher absorption observed in RSBC and CSBC (Liu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3c shows the FTIR spectra of SDBC, RSBC and CSBC. The broadband at 3430 cm −1 indicates phenolic hydroxyl groups or carboxylic acids in biochar (Liu, Ye, et al, 2022), and the absorption peak near 3640 cm −1 is the stretching vibration of -OH in CH (Yang et al, 2021).…”
Section: Characterization Of Biocharmentioning
confidence: 99%
“…The application of both biochar and calcium carbonate in cement has been explored. For the application of biochar in cement, two conclusions can be drawn from the many research findings available [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. First, biochar can be effectively used as an additive and as a replacement for cement in cement mortars.…”
Section: Introductionmentioning
confidence: 99%
“…Their results found that the combined use of early Portland cement and granulated blast furnace slag significantly improved the concrete’s early strength and chloride ion resistance. Yang et al [ 4 ] used various experimental methods to study the high-temperature resistance of cement-based materials added with biochar. Their research showed that as the biochar content increased, cracks in samples exposed to high temperatures decreased.…”
mentioning
confidence: 99%